2020
DOI: 10.1785/0220200022
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Deep Structures of Los Humeros Geothermal Field, Mexico, Using Three-Component Seismic Noise Beamforming

Abstract: We present a 1D shear-velocity model for Los Humeros geothermal field (Mexico) obtained from three-component beamforming of ambient seismic noise, imaging for the first time the bottom of the sedimentary basement ∼5  km below the volcanic caldera, as well as the brittle-ductile transition at ∼10  km depth. Rayleigh-wave dispersion curves are extracted from ambient seismic noise measurements and inverted using a Markov chain Monte Carlo scheme. The resulting probability density function provides the shear-veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(47 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…The selected minimum 1-D velocity model ( Figure 5) shows not only a good agreement with alternative studies on the region (Lermo et al, 2008;Löer et al, 2020) but also one possible geological boundary observed in retrieved well data (Norini et al, 2019). A prominent discontinuity is seen at ∼−1.2 km depth in Figure 5 for both Vp and Vs models.…”
Section: The 1-d Velocity Modelsupporting
confidence: 85%
See 3 more Smart Citations
“…The selected minimum 1-D velocity model ( Figure 5) shows not only a good agreement with alternative studies on the region (Lermo et al, 2008;Löer et al, 2020) but also one possible geological boundary observed in retrieved well data (Norini et al, 2019). A prominent discontinuity is seen at ∼−1.2 km depth in Figure 5 for both Vp and Vs models.…”
Section: The 1-d Velocity Modelsupporting
confidence: 85%
“…The seismicity presents a systematic shift toward 0.5–0.8 km greater depths and some improvements in clustering after the 1‐D inversion. Two velocity models proposed by Lermo et al (2008) ( P wave) and Löer et al (2020) ( S wave) are marked in green and magenta, respectively, in Figure 5a. The Vp model proposed by Lermo et al (2008) was derived using a seismic reflection profile and reaches an approximate depth of 0.5 km, below which a default value of 5.18 km/s is assigned.…”
Section: The 1‐d Velocity Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…The seismicity presents a systematic shift toward ∼0.5-0.8 km greater depths and some improvements in clustering after the 1-D inversion. Two velocity models proposed by Lermo et al (2008) (P wave) and Löer et al (2020) (S wave) are marked in green and magenta, respectively, in Figure 5a. The Vp model proposed by Lermo et al (2008) was derived using a seismic reflection profile and reaches an approximate depth of −0.5 km, below which a default value of 5.18 km/s is assigned.…”
Section: The 1-d Velocity Modelmentioning
confidence: 99%